Benthic macroinvertebrate community response to environmental changes over seven decades in an urbanized estuary in the northeastern United States. (July 2021) - Pelletier, Marguerite; Cobb, Donald; Rocha, Kenneth; Ho, Kay T.; Cantwell, Mark G.; Perron, Monique; Charpentier, Michael A.; Buffum, Henry W.; Hale, Stephen S.; Burgess, Robert M.
Abstract: Narragansett Bay is representative of New England, USA urbanized estuaries, with colonization in the early 17th century, and development into industrial and transportation centers in the late 18th and early 20th century. Increasing nationwide population and lack of infrastructure maintenance led to environmental degradation, and then eventual improvement after implementation of contaminant control and sewage treatment starting in the 1970s. Benthic macroinvertebrate community structure was expected to respond to these environmental changes. This study assembled data sets from the 1950s through 2010s to examine whether quantitative aggregate patterns in the benthic community corresponded qualitatively to stressors and management actions in the watershed. In Greenwich Bay and Providence River, patterns of benthic response corresponded to the decline and then improvement in sewage treatment at the Fields Point wastewater treatment plant. In Mount Hope Bay, the benthos corresponded to changes in bay fish populations due to thermal discharge from the Brayton Point power plant. The benthos of the Upper West Passage corresponded to climatic changes that caused regime shifts in the plankton and fish communities. Future work will examine the effects of further environmental improvements in the face of continued climatic changes and population growth. Highlights: Disparate data were assembled to provide a multi-decadal history of environmental changes in Narragansett Bay. Benthos in Greenwich Bay and Providence River responded to the decline and later improvement of sewage treatment. Benthos in Mount Hope Bay reflected changes in bay fish populations due to thermal discharge from a power plant. Benthos of the Upper West Passage responded to climatic changes that caused regime shifts in the plankton and fish. Future work will focus on the effects of environmental improvements in the face of continued climate and population change.